2018
DOI: 10.1098/rsif.2018.0594
|View full text |Cite
|
Sign up to set email alerts
|

Instability-driven oscillations of elastic microfilaments

Abstract: Cilia and flagella are highly conserved slender organelles that exhibit a variety of rhythmic beating patterns from non-planar cone-like motions to planar wave-like deformations. Although their internal structure, composed of a microtubule-based axoneme driven by dynein motors, is known, the mechanism responsible for these beating patterns remains elusive. Existing theories suggest that the dynein activity is dynamically regulated, via a geometric feedback from the cilium's mechanical deformation to the dynein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 58 publications
4
63
0
Order By: Relevance
“…De Canio et al 25 studied the linear stability and nonlinear dynamics of the clamped point follower load model of section 3.2.2 and found the same qualitative behavior we see in the clamped distributed follower force case. Ling et al 26 studied the linear stability and nonlinear dynamics of the 3D clamped case and found two distinct types of beating, a planar one similar to the one we observe and a helical one, each having its own instability threshold and a range of β in which it dominates. Fatehiboroujeni et al 46 studied the double-clamped 3D case, in which both ends of the filament are clamped and the base state is pre-buckled.…”
Section: Related Constrained Follower-force Problemssupporting
confidence: 69%
See 2 more Smart Citations
“…De Canio et al 25 studied the linear stability and nonlinear dynamics of the clamped point follower load model of section 3.2.2 and found the same qualitative behavior we see in the clamped distributed follower force case. Ling et al 26 studied the linear stability and nonlinear dynamics of the 3D clamped case and found two distinct types of beating, a planar one similar to the one we observe and a helical one, each having its own instability threshold and a range of β in which it dominates. Fatehiboroujeni et al 46 studied the double-clamped 3D case, in which both ends of the filament are clamped and the base state is pre-buckled.…”
Section: Related Constrained Follower-force Problemssupporting
confidence: 69%
“…Second, the 2D constraint may be relaxed to allow motion in 3D. Ling et al 26 found two distinct beating instabilities, one of them helical, in the constrained problem, however we are not aware of any such study for filament-cargo assemblies. Third, long-range hydrodynamic interactions may be included, e.g., by assuming the head is spherical and adding stresslets distributed along the filament [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve persistent motions, cyclic or oscillatory motions are needed, yet, the mechanism underlying the emergence of such oscillations remains unclear. Two major hypotheses, geometric feedback [8][9][10][11][12][13] and "flutter" or buckling instability [14][15][16][17][18] , have been raised based on theory and/or simulations: the first hypothesis assumes that a time-dependent dynein activity (switching on/off or modulation) is necessary to trigger the oscillations; the second one suggests that a steady point force or force distributions acting along the axial direction of a flexible filament can trigger its oscillatory motion through a "flutter" or buckling instability.…”
Section: Introductionmentioning
confidence: 99%
“…These instabilities have been the subject of recent theoretical and computational inquiries. Continuum as well as discrete agent-based models have been used to investigate the emergence of oscillations in single filaments, and coupling-induced synchrony in systems of two rotating filaments [29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%